Symptomatic description of transport and storage subsystem of manufacturing facility - Горяинов, Алексей Николаевич; Ковалёва, Наталья Ивановна (Eastern-European Journal of Enterprise Technologies, 2009)
A definition of the term "symptom" and its classification in the logistics system are offered. The symptoms in a diagnostic algorithm process are find out. The symptoms of transport and storage subsystem company are given